Construction of Hub Location Model Based on Genetic Algorithm - Hu, Liqin; Liu, Hong; Ying, Cao (Transportation research record, 2025)
This paper conducts an analysis of the cost composition of the China Railway Express train operation system, taking into account the choice of exit ports and the time value cost of goods during the operation of trains by China Railway Express. A site selection optimization model is then established with the objective of minimizing the total cost of the China Railway Express service network. A genetic algorithm is designed to solve the optimization model. The location model is then addressed using the designed algorithm, leading to the determination of the site selection plan for the central hub. The optimization results of the site selection plan are subsequently verified under different conditions. The node cities of the China Railway Express in China and the source cities of the freight trains are used as the objects of analysis during the process of solving the location model. The findings indicate that selecting Xi’an as the central hub and Chengdu as the sub-hub could result in an 18.1% reduction in the system cost of China Railway Express, while maintaining the advantage of logistics costs, particularly in scenarios where the freight subsidy is canceled. Furthermore, this choice ensures the stability of the logistics cost of the entire system, even in the event of serious congestion.